Workplace Accident Investigation of Finger Drops in Metal Manufacturing Industry Workers - Erna Agustin Sukmandari; Anggit Pratiwi (Proceeding of International Conference on Science, Health, And Technology, 2019)
Metal manufacturing industry is one industry that has a high risk for work accidents, both minor accidents, moderate, or severe accidents. Potential hazards that must be minimized so that workers can protect their safety and health. One way that can be used to overcome the danger is to use personal protective equipment (PPE). This study aims to analyze the work accidents that are removed by workers' fingers. Research using qualitative methods with case studies on workers who have work accidents. The main informants are workers who repair work accidents, while supporting informants are HSE managers in the industry. Data obtained through interviews conducted with key informants and supporting informants. Based on research data that can be done by workers who are disconnected in the finger segment due to being twisted by the threads that have been wasted from the gloves they use. At that time, the informant was looking for workpieces using a rotating machine. The informant is not aware of the thread being unraveled and takes machine turns so that it wraps around the fingers. The informant only knows that the finger was finished after finishing and took off the gloves. Inappropriate use of PPE will oppose workers. In addition, workers do not need work safety instructions, thus increasing the risk of workplace accidents.